Four-tier chemical bonding instrument: Its development and validation - Amalia, Elok; Habiddin, Habiddin (IAIN Palangka Raya, 2024)
This study highlights the development and validation of a four-tier instrument in chemical bonding to produce a valid and reliable instrument in the discipline. The instrument was developed according to the procedure proposed by Habiddin & Page (2019), including (1) mapping concept (2) testing & interviewing, (3) identifying & collecting student